Collaborative Biosynthesis of a Class of Bioactive Azaphilones by Two Separate Gene Clusters Containing Four PKS/NRPSs with Transcriptional Crosstalk in Fungi. Issue 11 (30th January 2020) - Huang, Xuenian; Zhang, Wei; Tang, Shen; Wei, Suhui; Lu, Xuefeng
Abstract: Azaphilones are a family of fungal polyketide metabolites with diverse chemical structures and biological activities with a highly oxygenated pyranoquinone bicyclic core. Here, a class of azaphilones possessing a 6/6/6/6 tetracyclic ring system was identified in Aspergillus terreus, and exhibited potential anticancer activities. The gene deletions and biochemical investigations demonstrated that these azaphilones were collaboratively synthesized by two separate clusters containing four core‐enzymes, two nonreducing PKSs, one highly reducing PKS, and one NRPS‐like. More interestingly, we found that the biosynthesis is coordinately regulated by a crosstalk mechanism between these two gene clusters based on three transcriptional factors. This is a meaningful mechanism of fungal secondary metabolism, which allows fungi to synthesize more complex compounds and gain new physiological functions. The results provide a new insight into fungal natural product biosynthesis. Abstract : Increasing complexity : Two separate clusters containing four core‐genes encoding two nrPKSs, one hrPKS, and one NRPS‐like enzyme, collaboratively synthesize a class of bioactive azaphilones in Aspergillus terreus . The biosynthesis is coordinated by collaborative transcriptional regulation based on three regulators in two clusters.